Modified porous silicon-based negative electrode material, preparation method thereof and lithium ion battery
Patent Information
- Application Number
- CN202311537638.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-11-17
AI Technical Summary
但随着脱锂/嵌锂的进行,硅颗粒巨大的体积膨胀,会导致碳层的破裂,使电解液与硅颗粒直接接触,导致电解液与硅之间发生副反应,导致碳包覆硅负极材料电化学性能的迅速衰减
(1)本发明的改性多孔硅基负极材料包括内核和外壳,内核为多孔硅内核,外壳为氮和氟双掺杂的碳外壳,内核和外壳的至少部分区域连接,且内核和外壳之间为空腔结构。该结构中内核与外壳之间的空腔结构为硅的体积膨胀预留了空间,且多孔硅颗粒内部的孔隙结构能够为硅的体积膨胀预留出更多空间,使该改性多孔硅负极材料具有更优异的结构稳定性和循环性能;此外,通过对碳外壳的氮、氟双掺杂,使得硅基负极材料具有更明显的赝电容效应,使得该改性多孔硅负极材料具有更优异的电化学性能。
Smart Images

Figure CN117276519B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials technology, specifically relating to silicon-based anode materials with no volume expansion and stable cycle performance, their preparation methods, and lithium-ion batteries. Background Technology
[0002] Lithium-ion batteries, as a clean energy storage system, are widely used in electronic devices, transportation, and grid energy storage. To achieve lightweight lithium-ion batteries, silicon-based anode materials can replace traditional graphite anode materials. Silicon-based anode materials are considered the preferred material for next-generation lithium-ion battery anodes due to their ultra-high theoretical lithium intercalation capacity. However, the huge volume change (300-400%) during lithium intercalation / deintercalation in silicon-based anode materials causes silicon particles to break down during battery charge-discharge cycles, ultimately leading to a rapid decline in the electrochemical performance of the silicon-based anode material. Therefore, solving the expansion problem of silicon-based anodes is the primary issue for realizing the commercial application of silicon-based anodes.
[0003] The expansion of silicon particles leads to the formation of an unstable solid electrolyte interphase (SEI), which rapidly consumes the electrolyte, resulting in a rapid decline in the electrochemical performance of silicon-based anodes. Carbon coating can prevent direct contact between silicon and the electrolyte, reducing electrolyte consumption. However, with the progress of lithium delithiation / intercalation, the massive volume expansion of silicon particles can cause the carbon layer to rupture, allowing direct contact between the electrolyte and silicon particles. This leads to side reactions between the electrolyte and silicon, resulting in a rapid decline in the electrochemical performance of carbon-coated silicon anode materials. Therefore, carbon coating alone cannot effectively solve the short service life defect of silicon-based anodes. Summary of the Invention
[0004] To address the aforementioned technical problems, the present invention aims to provide a modified porous silicon-based anode material, its preparation method, and a lithium-ion battery.
[0005] To achieve the above objectives, the present invention proposes the following solution: One of the objectives of this invention is to provide a modified porous silicon-based anode material, comprising a core, a shell, and a cavity, wherein the core is a porous silicon-containing core, the shell is a nitrogen- and fluorine-doped carbon shell, the cavity is located between the core and the shell, and at least a portion of the core and the shell are connected.
[0006] Preferably, the porous silicon-containing core is a single porous secondary particle or an agglomeration composed of multiple porous secondary particles, wherein the porous secondary particles are formed by the aggregation of one or more primary particles; the porous silicon-containing core is made of one or more of silicon, silicon suboxide, and silicon-containing alloys.
[0007] Preferably, the porous silicon-containing core accounts for 45-80% of the mass of the modified porous silicon-based anode material, and the nitrogen- and fluorine-doped carbon shell accounts for 20-55% of the mass of the modified porous silicon-based anode material.
[0008] As a general inventive concept, this invention also provides a method for preparing a modified porous silicon-based anode material, comprising: (1) Carbon is coated on the surface of silicon-containing particles to obtain a precursor; (2) At the reaction temperature, NF3 / Ar mixed gas is introduced to allow NF3 to react with the precursor and obtain modified porous silicon-based anode material.
[0009] Preferably, in step (2), the reaction temperature is 100~400℃; and the volume fraction of NF3 gas in the NF3 / Ar mixed gas is 5~15%.
[0010] Preferably, the silicon-containing particles are made of one or more of silicon, silicon suboxide, and silicon-containing alloys; the size of the silicon-containing particles is 1 nm to 100 μm.
[0011] Preferably, the silicon content in the silicon-containing alloy is 20-60% by mass; the silicon-containing alloy is an iron-silicon alloy or an aluminum-silicon alloy.
[0012] Preferably, in step (1), the carbon content in the precursor is 10-20% by mass.
[0013] Preferably, in step (1), the coating of carbon on the surface of silicon-containing particles is achieved by method one or method two; Method 1 involves first coating the surface of silicon-containing particles with a carbon precursor, and then carbonizing the silicon-containing particles coated with the carbon precursor in an inert gas. Method 2 involves decomposing a carbon source gas and depositing it onto the surface of silicon-containing particles to achieve carbon coating on the surface of the silicon-containing particles.
[0014] As a preferred option, Method 1 includes: S1. Mix silicon-containing particles, carbon source, and solvent, and carry out a hydrothermal reaction. After the carbon source decomposes, a layer of carbon precursor is coated on the surface of the silicon-containing particles. S2. The material obtained from the hydrothermal reaction is washed, separated into solid and liquid components, and dried to obtain carbon precursor-coated silicon particles. S3. Carbon-coated silicon particles are carbonized in an inert or nitrogen atmosphere to obtain carbon-coated silicon particles.
[0015] As a preferred embodiment, in Method 1, the mass ratio of silicon particles to carbon source is 100:(10~200).
[0016] Preferably, in Method 1, the temperature of the hydrothermal reaction is 100~200℃; the time of the hydrothermal reaction is 1~24h; and the volume of the solvent accounts for 1 / 3~2 / 3 of the volume of the hydrothermal reactor.
[0017] Preferably, in method one, the decomposition temperature of the carbon source is 100~200℃; the carbon source is one or more of glucose, sucrose, fructose, citric acid, oxalic acid, graphene, carbon nanotubes, asphalt, phenolic resin, and epoxy resin; and the solvent is one or more of water, ethanol, methanol, tetrahydrofuran, and N,N-dimethylformamide.
[0018] Preferably, in method one, the carbonization temperature is 400~1000℃.
[0019] As a preferred option, method two includes: Silicon-containing particles are placed in a furnace, and carbon source gas is introduced into the furnace, causing the carbon source gas to decompose and deposit on the surface of the silicon-containing particles, thus obtaining carbon-coated silicon particles.
[0020] Preferably, in Method 2, the carbon source gas is one or more of ethanol, methanol, benzene, methane, ethane, ethylene, acetylene, carbon dioxide, argon, helium, and nitrogen. Preferably, in method two, the temperature at which the carbon source gas decomposes and deposits is 600~800℃.
[0021] Preferably, in method two, the furnace atmosphere is non-oxidizing. Preferably, before introducing carbon source gas into the furnace, the air in the furnace is first purged with inert gas. Preferably, after stopping the introduction of carbon source gas into the furnace (i.e., after stopping the reaction), inert gas is continued to be introduced into the material during the cooling process to prevent the carbon-coated silicon particles from reacting with the air.
[0022] As a general inventive concept, the present invention also provides a lithium secondary battery, including the aforementioned modified porous silicon-based anode material or the modified porous silicon-based anode material prepared by the aforementioned preparation method.
[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) The modified porous silicon-based anode material of the present invention includes a core and a shell. The core is a porous silicon core, and the shell is a nitrogen- and fluorine-doped carbon shell. At least a portion of the core and the shell are connected, and there is a cavity structure between the core and the shell. The cavity structure between the core and the shell in this structure provides space for the volume expansion of silicon, and the pore structure inside the porous silicon particles can provide more space for the volume expansion of silicon, so that the modified porous silicon anode material has better structural stability and cycle performance. In addition, by doping the carbon shell with nitrogen and fluorine, the silicon-based anode material has a more obvious pseudocapacitive effect, so that the modified porous silicon anode material has better electrochemical performance.
[0024] (2) In this invention, a carbon coating layer is first formed on the surface of silicon particles, and then NF3 gas is used to react with the grain boundaries inside the silicon particles under low temperature conditions. On the one hand, the reaction with the surface of the silicon particles inside reduces the size of the silicon particles and increases the bulk diffusion coefficient of lithium ions in the silicon-based particles. On the other hand, not only is a cavity structure formed between the silicon particles and the carbon coating layer on the surface, but the interior of the silicon particles is also made into a porous structure, which reserves space for the volume expansion of the silicon substrate and improves its structural stability, cycle stability and electrochemical performance. In addition, NF3 gas achieves nitrogen and fluorine dual doping of the carbon coating layer on the surface, which makes the silicon-based anode material have a more obvious pseudocapacitive effect and improves its electrochemical performance. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 The images are TEM images of materials at different stages in Example 1, where (a), (b), and (c) correspond to the original solid silicon nanoparticles, the intermediate product carbon-coated silicon, and the Yolk-shell structure porous silicon / nitrogen-fluorine dual-doped carbon composite anode material, respectively.
[0027] Figure 2 The images show the SEM images and elemental mapping diagrams of the porous silicon / nitrogen-fluorine dual-doped carbon composite anode material with a Yolk-shell structure obtained in Example 1. (a) is the SEM image, and (b), (c), (d), (e), and (f) are the elemental mapping diagrams of silicon, oxygen, carbon, fluorine, and nitrogen, respectively.
[0028] Figure 3 This is a schematic diagram illustrating the process of preparing a porous silicon / nitrogen-fluorine dual-doped carbon composite anode material with a Yolk-shell structure in Example 1 of the present invention.
[0029] Figure 4 This is a comparison graph showing the cycle performance curves of the coin cell assembled with the negative electrode material obtained in Example 1 and commercially available silicon material. Detailed Implementation
[0030] This invention provides a modified porous silicon-based anode material, comprising a core, a shell, and a cavity. The core is a porous silicon-containing core, the shell is a nitrogen- and fluorine-doped carbon shell, and the cavity is located between the core and the shell, with at least a portion of the core and shell connected. This structure provides space for the volume expansion of the silicon-containing core, and the porous structure within the porous silicon-containing core allows for even more space for silicon volume expansion, resulting in superior structural stability and cycle performance of the modified porous silicon anode material. Furthermore, the nitrogen- and fluorine doping of the carbon shell enhances the pseudocapacitive effect of the silicon-based anode material, leading to superior electrochemical performance. The porous silicon-containing core has a porous structure both on its surface and internally.
[0031] In some preferred embodiments, the porous silicon-containing core is a single porous secondary particle or an agglomeration composed of multiple porous secondary particles, wherein the porous secondary particle is formed by the aggregation of one or more primary particles.
[0032] In some preferred embodiments, the porous silicon-containing core is made of one or more of silicon, silicon suboxide, and silicon-containing alloys. The silicon-containing alloy can be an iron-silicon alloy, an aluminum-silicon alloy, etc., and preferably, the silicon content in the silicon-containing alloy is 20-60% by mass, for example, 25%, 30%, 35%, 40%, 45%, 50%, 55%, etc., wherein the SiO2 content is between Si and SiO2. x 0 < x < 2 all fall under the category of silicon suboxide.
[0033] In some preferred embodiments, the porous silicon-containing core accounts for 45-80% of the mass of the modified porous silicon-based anode material, for example, 42%, 45%, 48%, 50%, 53%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, etc., and the nitrogen- and fluorine-doped carbon shell accounts for 20-55% of the mass of the modified porous silicon-based anode material, for example, 23%, 25%, 28%, 30%, 32%, 35%, 37%, 40%, 42%, 45%, 48%, 50%, 53%, etc. If the silicon mass percentage is too high, its electrochemical stability deteriorates; if the percentage is too low, its electrochemical capacity decreases.
[0034] This invention also provides a method for preparing a modified porous silicon-based anode material, comprising: (1) Carbon is coated on the surface of silicon-containing particles to obtain a precursor; (2) At the reaction temperature, NF3 / Ar mixed gas is introduced to react NF3 with the precursor to obtain modified porous silicon-based anode material.
[0035] In this method, NF3 gas reacts with the grain boundaries inside the silicon particles in the precursor under low-temperature conditions. On the one hand, it reacts with the surface of the internal silicon particles, thereby reducing the size of the silicon-containing particles and improving the bulk diffusion coefficient of lithium ions in the silicon-based particles. On the other hand, it not only forms a cavity structure between the silicon particles and the carbon coating layer on the surface, but also makes the interior of the silicon particles porous, reserving space for the volume expansion of the silicon substrate, thereby improving its structural stability, cycle stability and electrochemical performance. In addition, NF3 gas achieves nitrogen and fluorine dual doping of the carbon coating layer on the surface of the precursor, making the silicon-based anode material have a more obvious pseudocapacitive effect and improving its electrochemical performance.
[0036] In some preferred embodiments, in step (2), the reaction temperature is 100~400℃, more preferably 200~350℃, such as 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, 270℃, 280℃, 290℃, 300℃, 310℃, 320℃, 330℃, 340℃, etc.; when the temperature is too low, the reaction time is too long and the efficiency is low; when the temperature is too high, the reaction time is too short and the reaction process is difficult to control; the volume fraction of NF3 gas in the NF3 / Ar mixed gas is 5~15%.
[0037] In some preferred embodiments, in step (1), the carbon content in the precursor is 10-20%, for example, 10%, 10.5%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc.
[0038] In some preferred embodiments, the silicon-containing particles are one or more of silicon, silicon suboxide, and silicon-containing alloys, wherein the silicon-containing alloy can be an iron-silicon alloy, an aluminum-silicon alloy, etc., and preferably the silicon-containing alloy contains 20-60% silicon by mass, wherein the SiO2 composition is between Si and SiO2. x 0 < x < 2 all fall under the category of silicon suboxide; the size of the silicon-containing particles is 10 nm to 100 μm, more preferably 10 nm to 1 μm, and even more preferably 10 nm to 200 nm, such as 30 nm, 50 nm, 70 nm, 100 nm, 120 nm, 150 nm, 180 nm, etc.
[0039] In some preferred embodiments, in step (1), the coating of carbon on the surface of silicon-containing particles is achieved by method one or method two; Method 1 involves first coating the surface of silicon-containing particles with a carbon precursor, and then carbonizing the silicon-containing particles coated with the carbon precursor in nitrogen or an inert gas. Method 2 involves decomposing carbon source gas and depositing it onto the surface of silicon-containing particles to achieve carbon coating on the surface of silicon-containing particles.
[0040] In some preferred embodiments, after carbon is deposited on the surface of silicon-containing particles using method two, the carbon source gas is stopped, and nitrogen or inert gas is introduced for protective cooling. After cooling to 100~400℃, an NF3 / Ar mixed gas is introduced for a heat preservation reaction. The carbon deposition in step (1) and step (2) can be carried out in the same furnace, requiring only a change in the gas source. This process is simple, short, and highly versatile, making it suitable for large-scale industrial production. Of course, it is also possible to introduce nitrogen or inert gas for protective cooling to room temperature, then raise the temperature to 100~400℃, and then introduce an NF3 / Ar mixed gas for a heat preservation reaction. This method, however, is more complex.
[0041] When using Method 1, silicon-containing particles coated with carbon precursors are carbonized in a furnace under nitrogen or inert gas, followed by further cooling with nitrogen or inert gas until the temperature reaches 100-400°C, then an NF3 / Ar mixed gas is introduced for a heat-holding reaction. Step (1) carbonization and step (2) can be carried out in the same furnace, requiring only a change in the gas source. This method is simple, has a short process, is highly versatile, and is suitable for large-scale industrial production. Alternatively, after cooling to room temperature with nitrogen or inert gas, the temperature can be raised to 100-400°C, followed by the introduction of an NF3 / Ar mixed gas for a heat-holding reaction. This method, however, is more complex.
[0042] In this invention, any conventional furnace capable of achieving sealing and atmosphere switching can be selected as the reactor, such as a tube furnace. The material can be placed in a burning boat first and then placed in the tube furnace, or it can be placed in other carriers and then placed in the tube furnace.
[0043] The inert gas can be a conventional inert gas, including the most commonly used argon, or other inert gases such as helium.
[0044] In some preferred embodiments, method one includes: S1. Mix silicon-containing particles, carbon source, and solvent, and carry out a hydrothermal reaction. After the carbon source decomposes, a layer of carbon precursor is coated on the surface of the silicon-containing particles. S2. The material in the hydrothermal reactor is washed, centrifuged and dried to obtain carbon precursor coated silicon particles. S3. Carbon-coated silicon particles are carbonized in an inert or nitrogen atmosphere to obtain carbon-coated silicon particles.
[0045] In some preferred embodiments, the mass ratio of silicon particles to carbon source is 100:(10~200).
[0046] The amount of solvent used can be based on the amount of solvent used in conventional hydrothermal reactions; in some embodiments, the volume of the solvent accounts for 1 / 3 to 2 / 3 of the volume of the hydrothermal reactor.
[0047] In some preferred embodiments, the carbon source decomposition temperature is 100~200℃; the carbon source decomposition time is 1~24h.
[0048] In some preferred embodiments, the carbon source is one or more of glucose, sucrose, fructose, citric acid, oxalic acid, graphene, carbon nanotubes, asphalt, phenolic resin, and epoxy resin.
[0049] In some preferred embodiments, the solvent is one or more of water, ethanol, methanol, tetrahydrofuran, and N,N-dimethylformamide.
[0050] In some preferred embodiments, the carbonization temperature is 400~1000℃. The carbonization temperature may vary depending on the carbon source, but as long as carbonization can be achieved within this temperature range, it is acceptable.
[0051] In some preferred embodiments, method two includes: placing silicon-containing particles in a furnace, introducing carbon source gas into the furnace, and causing the carbon source gas to decompose and deposit on the surface of the silicon-containing particles to obtain carbon-coated silicon particles.
[0052] In some preferred embodiments, the carbon source gas is one or more of ethanol, methanol, benzene, methane, ethane, ethylene, acetylene, and carbon monoxide, and the carrier gas of the carbon source gas is one or more of argon, helium, and nitrogen. The decomposition and deposition temperature of the carbon source gas is 600~800℃. When the temperature is too low, it is difficult to decompose organic matter into single-atom carbon, and when the temperature is too high, the decomposition rate of organic gas is too fast, making it difficult to control the reaction process. The decomposition and deposition time of the carbon source gas can be flexibly controlled according to the carbon content requirements in the obtained carbon-coated silicon-containing particle precursor.
[0053] To facilitate understanding of the present invention, the invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0054] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0055] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0056] like Figure 1As shown, silicon-containing particles are subjected to chemical vapor deposition (CVD) to decompose a carbon source gas at a certain temperature and deposit a carbon layer on the surface of the silicon particles. Then, at a certain temperature, an NF3 / Ar mixed gas is introduced. NF3 preferentially reacts with the grain boundaries of silicon, and then with the internal grains of silicon, thus forming a void layer between the silicon core and the carbon layer. Simultaneously, the silicon core contains numerous voids. Furthermore, NF3 causes the carbon to be doped with both nitrogen and fluorine. No other processing steps are required to obtain the anode material.
[0057] Example 1 This embodiment includes the following steps: Step S1: 0.2 g of nano-silicon powder with a particle size of 50~150 nm (TEM image shown) Figure 1 (a) The sample is placed on an alumina sintering boat and placed in a tube furnace. Argon gas is introduced at a flow rate of 100 mL / min for 60 min to purge the air from the tube furnace. The temperature inside the tube furnace is then raised from room temperature to 800°C at a heating rate of 10°C / min and held at that temperature. Then the argon gas is stopped.
[0058] Step S2: An acetylene / argon mixture containing 10 vol% acetylene is introduced into the tube furnace from step S1 at a gas flow rate of 100 mL / min to initiate the reaction. After 20 min, the furnace is allowed to cool naturally, and the introduction of the acetylene / argon mixture is stopped. Argon gas is then introduced at a gas flow rate of 100 mL / min to obtain the intermediate product, carbon-coated silicon particles. TEM image shown below. Figure 1 As shown in (b), the mass percentage of carbon in the intermediate product was 12%, and the mass percentage of silicon particles was 88%.
[0059] Step S3: When the temperature of the tubular furnace in step S2 drops to 350°C, start heat preservation, stop the argon gas supply, and start the NF3 / argon gas mixture containing 5 vol% NF3 at a gas flow rate of 100 mL / min for 8 hours.
[0060] In step S4, the tube furnace in step S3 is allowed to cool naturally, and the NF3 / argon mixture is stopped. At the same time, argon is introduced at a gas flow rate of 100 mL / min until the tube furnace cools to room temperature. The material on the burning boat is removed to obtain a porous silicon / nitrogen-fluorine dual-doped carbon composite anode material with a Yolk-shell structure. In the composite anode material, the mass ratio of the porous silicon core is 76%, and the mass ratio of the nitrogen-fluorine dual-doped carbon shell is 24%.
[0061] TEM images of the porous silicon / nitrogen-fluorine dual-doped carbon composite anode material are shown below. Figure 1As shown in (c), the material consists of an outer shell, a core, and a cavity between the outer shell and the core. The lighter-colored areas in the core are pores. The TEM bright-field phase diagram and elemental mapping diagram are shown below. Figure 2 As shown in the figure, the core of the material is silicon, and the surface of the core is naturally oxidized by oxygen in the air; the outer shell is mainly carbon, with a small amount of nitrogen and fluorine present at the same time, indicating that nitrogen and fluorine have achieved carbon doping.
[0062] Example 1: A schematic diagram of the process for preparing a porous silicon / nitrogen-fluorine dual-doped carbon composite anode material with a Yolk-shell structure is shown below. Figure 3 As shown, after coating a solid nano-silicon particle with a carbon layer, the carbon-coated silicon particle is then treated with NF3 gas. The NF3 gas first contacts the carbon shell, and the highly reactive nitrogen and fluorine atoms easily form bonds with the defective carbon atoms in the carbon layer, thus obtaining a nitrogen-fluorine dual-doped carbon layer. The NF3 gas enters the interface between the carbon layer and the silicon particle through the carbon layer, and the following reaction occurs: NF3(g) + Si(s) → N2(g) + SiF4(g). Therefore, the silicon nucleus is etched to reduce its volume, and no solid products remain in the material. The silicon particle is polycrystalline silicon with abundant grain boundaries. The interfacial energy at the grain boundaries is the highest, and it will preferentially react with NF3, thus forming abundant pores at the grain boundaries.
[0063] The negative electrode material obtained in Example 1 and commercially available silicon powder were assembled into a coin cell using conventional methods in the art, and the electrochemical performance of the coin cell was tested. Figure 4 The cycle performance diagram of the coin cell is shown below. Figure 4 As can be seen, under a charge-discharge rate of 0.5 A / g and a cutoff voltage of 0.01~1 V, after 100 cycles, the battery assembled with the negative electrode material obtained in Example 1 maintains a discharge specific capacity of over 2248.2 mAh / g, while the battery containing commercially available silicon powder only has a capacity of 654.6 mAh / g after 100 cycles. The negative electrode material prepared in Example 1 exhibits excellent cycle stability, with a capacity retention rate of 98.9% after 100 charge-discharge cycles.
[0064] Example 2 This embodiment includes the following steps: Step S1: Add 0.2 g of nano-silicon powder with a particle size of 50~150nm and 0.15 g of phenolic resin to a 250mL beaker, then add 60mL of ethanol, stir for 30min, and then transfer the suspension in the beaker to a 100mL stainless steel hydrothermal reactor lined with polytetrafluoroethylene.
[0065] Step S2: Heat the drying oven to 160°C and keep it warm. Transfer the hydrothermal reactor from step S1 into the drying oven and keep it warm for 24 hours. Then remove the hydrothermal reactor and let it cool naturally to room temperature.
[0066] In step S3, the suspension in the hydrothermal reactor in step S2 is filtered, washed, and dried to obtain an intermediate product. The intermediate product contains 20.0% carbon and 80.0% silicon particles by mass.
[0067] Step S4: Place the intermediate product obtained in step S3 on an alumina sintering boat, and place the sintering boat in a tube furnace. Introduce argon gas at a flow rate of 100 mL / min to purge the air from the tube furnace. Simultaneously, raise the temperature inside the tube furnace from room temperature to 800°C at a heating rate of 10°C / min and hold for 2 hours. Then, cool the furnace to 300°C and hold.
[0068] In step S5, the argon gas flow to the tube furnace in step S4 is stopped, and a gas mixture containing 5 vol% NF3 and argon gas is introduced at a gas flow rate of 100 mL / min for 12 hours. Then, the NF3 / argon gas flow is stopped, and the tube furnace is allowed to cool naturally. At the same time, argon gas is introduced at a gas flow rate of 100 mL / min until the tube furnace cools to room temperature. The material on the burning boat is removed to obtain a porous silicon / nitrogen-fluorine dual-doped carbon composite anode material with a Yolk-shell structure. In the composite anode material, the mass ratio of the porous silicon core is 47.9%, and the mass ratio of the nitrogen-fluorine dual-doped carbon shell is 52.1%.
[0069] Example 3 The only difference between this embodiment and embodiment 1 is that in step S5, the heat preservation temperature is 100℃, the NF3 / argon mixture is introduced for 24 hours, and the NF3 / argon mixture contains 15 vol of NF3.
[0070] Example 4 The only difference between this embodiment and Embodiment 1 is that in step S5, the heat preservation temperature is 400℃ and the NF3 / argon gas mixture is introduced for 2 hours.
[0071] Example 5 The only difference between this embodiment and Embodiment 1 is that in step S1, the temperature is raised to 1000℃ and then held; in step S2, a methane / argon mixture containing 5 vol% methane is introduced into the tube furnace in step S1 at a gas flow rate of 100 mL / min to carry out the reaction. After 10 min, the furnace is allowed to cool down naturally, and the introduction of the methane / argon mixture is stopped. Argon is then introduced at a gas flow rate of 100 mL / min to obtain the intermediate product carbon-coated silicon particles.
[0072] Example 6 The only difference between this embodiment and Embodiment 1 is that in step S1, the temperature is raised to 900°C and then held at that temperature; in step S2, an ethylene / argon mixture containing 5 vol% ethylene is introduced into the tube furnace in step S1 at a gas flow rate of 100 mL / min to carry out the reaction. After 15 min, the furnace is allowed to cool down naturally, and the introduction of the ethylene / argon mixture is stopped. Argon is then introduced at a gas flow rate of 100 mL / min to obtain the intermediate product, carbon-coated silicon particles.
[0073] Example 7 This embodiment includes the following steps: Step S1: Add 0.2 g of silicon powder with a particle size of 150~400 nm and 0.2 g of fructose to a 250 mL beaker, then add 60 mL of ethanol, stir for 30 min, and then transfer the suspension in the beaker to a 100 mL stainless steel hydrothermal reactor lined with polytetrafluoroethylene.
[0074] Step S2: Heat the drying oven to 180°C and keep it warm. Transfer the hydrothermal reactor from step S1 into the drying oven and keep it warm for 12 hours. Then remove the hydrothermal reactor and let it cool naturally to room temperature.
[0075] Step S3: The suspension in the hydrothermal reactor in step S2 is filtered, washed and dried to obtain an intermediate product. The intermediate product contains 15% carbon by mass and 85% silicon particles by mass.
[0076] Step S4: Place the intermediate product obtained in step S3 on an alumina sintering boat, and place the sintering boat in a tube furnace. Introduce argon gas at a flow rate of 100 mL / min to purge the air from the tube furnace. Simultaneously, raise the temperature inside the tube furnace from room temperature to 800°C at a heating rate of 10°C / min and hold for 2 hours. Then, cool the furnace to 300°C and hold.
[0077] In step S5, the argon gas flow to the tube furnace in step S4 is stopped, and a gas mixture containing 5 vol% NF3 and argon gas is introduced at a gas flow rate of 100 mL / min for 8 h. Then, the NF3 / argon gas flow is stopped, and the tube furnace is allowed to cool naturally. At the same time, argon gas is introduced at a gas flow rate of 100 mL / min until the tube furnace cools to room temperature. The material on the burning boat is removed to obtain a porous silicon / nitrogen-fluorine dual-doped carbon composite anode material with a Yolk-shell structure. In the composite anode material, the porous silicon core accounts for 70% of the mass, and the nitrogen-fluorine dual-doped carbon shell accounts for 30% of the mass.
[0078] The negative electrode material obtained in Example 2 was assembled into a coin cell using conventional methods in the art, and the electrochemical performance of the coin cell was tested. At a current density of 0.1 A / g, the initial discharge specific capacity was 1482.9 mAh / g, and the initial coulombic efficiency was 54.5%. After 250 cycles at a charge-discharge rate of 0.5 A / g and a cutoff voltage of 0.01–1 V, the battery containing the negative electrode material obtained in Example 2 maintained a discharge specific capacity of over 509.0 mAh / g, with a capacity retention of 75.2%.
[0079] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A modified porous silicon-based anode material, characterized in that, It includes a core, a shell, and a cavity. The core is a porous silicon-containing core, the shell is a nitrogen- and fluorine-doped carbon shell, and the cavity is located between the core and the shell, with at least a portion of the core and the shell connected. The porous silicon-containing core is a single porous secondary particle or an agglomeration of multiple porous secondary particles, wherein the porous secondary particles are formed by the aggregation of multiple primary particles.
2. The modified porous silicon-based anode material as described in claim 1, characterized in that, The porous silicon-containing core is made of one or more of silicon, silicon suboxide, and silicon-containing alloys.
3. The modified porous silicon-based anode material as described in claim 1 or 2, characterized in that, The porous silicon-containing core accounts for 45-80% of the mass of the modified porous silicon-based anode material, and the nitrogen and fluorine dual-doped carbon shell accounts for 20-55% of the mass of the modified porous silicon-based anode material.
4. A method for preparing a modified porous silicon-based anode material, characterized in that, include: (1) Carbon is coated on the surface of silicon-containing particles to obtain a precursor; (2) At the reaction temperature, an NF3 / Ar mixed gas is introduced to react NF3 with the precursor to obtain a modified porous silicon-based anode material; the volume fraction of NF3 gas in the NF3 / Ar mixed gas is 5~15%; the reaction temperature is 100~400℃.
5. The method for preparing the modified porous silicon-based anode material as described in claim 4, characterized in that, In step (2), the reaction time is 2 to 24 hours.
6. The method for preparing the modified porous silicon-based anode material as described in claim 4, characterized in that, The silicon-containing particles are made of one or more of silicon, silicon suboxide, and silicon-containing alloys; the particle size of the silicon-containing particles is 10 nm to 100 μm.
7. The method for preparing the modified porous silicon-based anode material as described in claim 6, characterized in that, The silicon content in the silicon-containing alloy is 20-60% by mass; the silicon-containing alloy is an iron-silicon alloy or an aluminum-silicon alloy.
8. The method for preparing the modified porous silicon-based anode material as described in claim 4, characterized in that, The precursor contains 10-20% carbon by mass.
9. The method for preparing the modified porous silicon-based anode material as described in claim 4, characterized in that, In step (1), the coating of carbon on the surface of silicon-containing particles is achieved by method one or method two; Method 1 includes: first coating the surface of silicon-containing particles with a carbon precursor, and then carbonizing the silicon-containing particles coated with the carbon precursor in an inert gas. Method 2 includes: decomposing and depositing carbon source gas onto the surface of silicon-containing particles to achieve carbon coating on the surface of silicon-containing particles.
10. The method for preparing the modified porous silicon-based anode material as described in claim 9, characterized in that, Method 1 includes: S1. Mix silicon-containing particles, carbon source, and solvent to carry out a hydrothermal reaction; S2. The material obtained from the hydrothermal reaction is subjected to solid-liquid separation, washing and drying to obtain carbon precursor coated silicon particles; S3. Carbon precursor-coated silicon particles are carbonized in an inert atmosphere or a nitrogen atmosphere to obtain carbon-coated silicon particles. Method 2 includes: Silicon-containing particles are placed in a furnace, and carbon source gas is introduced into the furnace, causing the carbon source gas to decompose and deposit on the surface of the silicon-containing particles, thus obtaining carbon-coated silicon particles.
11. The method for preparing the modified porous silicon-based anode material as described in claim 10, characterized in that, In Method 1, the mass ratio of silicon particles to carbon source is 100:(10~200); the temperature of the hydrothermal reaction is 100~200℃; and the time of the hydrothermal reaction is 1~24h.
12. The method for preparing the modified porous silicon-based anode material as described in claim 10, characterized in that, In Method 1, the decomposition temperature of the carbon source is 100~200℃; the carbon source is one or more of glucose, sucrose, fructose, citric acid, oxalic acid, graphene, carbon nanotubes, asphalt, phenolic resin, and epoxy resin.
13. The method for preparing the modified porous silicon-based anode material as described in claim 10, characterized in that, In Method 1, the solvent is one or more of water, ethanol, methanol, tetrahydrofuran, and N,N-dimethylformamide.
14. The method for preparing the modified porous silicon-based anode material as described in claim 10, characterized in that, In Method 1, the carbonization temperature is 400~1000℃.
15. The method for preparing the modified porous silicon-based anode material as described in claim 10, characterized in that, In Method 2, the carbon source gas is one or more of ethanol, methanol, benzene, methane, ethane, ethylene, acetylene, and carbon monoxide; the carrier gas of the carbon source gas is one or more of argon, helium, and nitrogen.
16. The method for preparing the modified porous silicon-based anode material as described in claim 10, characterized in that, In Method 2, the temperature at which the carbon source gas decomposes and deposits is 600~800℃.
17. A lithium secondary battery, characterized in that, It includes the modified porous silicon-based anode material as described in any one of claims 1 to 3, or the modified porous silicon-based anode material prepared by the preparation method as described in any one of claims 4 to 16.
Citation Information
Patent Citations
Lithium ion battery negative electrode material and preparation method thereof
CN103872330A
Fluorine-nitrogen doped amorphous carbon coated silicon-carbon composite material and preparation method thereof
CN116314722A